Knowledge and attitude on consumption of iron supplement among pregnant women in Kuala terengganu, Terengganu - Chai, Ern Theng; Noor Salihah Zakaria; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2017)
The high prevalence of iron deficiency anemia and low compliance of iron supplement was reported among pregnant women in Malaysia. This study aimed to determine the knowledge and attitude on consumption of iron supplement among pregnant women in Kuala Terengganu. A cross-sectional study was carried out in government clinics and hospital. Pregnant women aged from 15-49 (n=120) were interviewed using self-administered questionnaires. Descriptive statistics and non-parametric tests were used. Majority of pregnant women consumed iron supplement during the pregnancy (77.5%). Only 18.3% of pregnant women do not consumed iron supplement and another 4.2% not sure whether they consumed iron supplement. The prevalence of anemia in this study was low (19.2%). The level of knowledge and attitude on consumption of iron supplement was high, 58.3% and 54.2%, respectively. The level of knowledge on consumption of iron supplement was highly associated with the consumption of iron supplement (χ2= 16.717, p< 0.001). Furthermore, level of attitude on consumption of iron supplement also showed an association with the consumption of iron supplement (χ2= 8.449, p< 0.01). The data could serve as an early evidence related to the knowledge and attitude on consumption of iron supplement among pregnant women in Terengganu.